PLATELET-RICH PLASMA IN DERMAL REMODELING: A PROSPECTIVE REAL-WORLD CASE SERIES INTEGRATING CLINICAL AND PATIENT-REPORTED OUTCOMES - Majowicz-Czaszyńska, Karolina; Łoś, Aleksandra; Król, Nikola; Jakubczyk, Inga; Szkodziński, Kacper; Maternia, Jagoda; Pempuś, Wiktoria; Blok, Aleksandra; Wiater, Dominik; Płodzień, Gabriela; Tomaszek, Barbara (International Journal of Innovative Technologies in Social Science, 2026)
Background: Platelet-rich plasma (PRP) is a modality recognized in the field of dermatology for its regenerative properties. However, there is significant clinical variety, particularly on patient-reported outcomes and real-world effectiveness across indications. Objective: The aim of this prospective observational case series was to evaluate the efficacy of PRP therapy in real-life clinical setting based on clinician-assessed and patient-reported outcomes. Methods: Fifty patients received autologous PRP treatment between January and June 2019. PRP was prepared using a standardized centrifugation process and applied as intradermal injections at 3-4 weeks intervals. Clinical indications included striae distensae, post-traumatic and burn scars, and skin quality concerns. Standardized clinical photography, retrospective observer-based Patient and Observer Scar Assessment Scale (POSAS) scoring, and a structured patient-reported outcome (PRO) instrument assessing perceived efficacy and satisfaction were used to evaluate outcomes. Descriptive analysis was performed, including summary statistics of PRO and POSAS score changes in representative cases. Results: The results of PRP treatment were variable, but mostly positive. The most consistent results were improvements in skin texture, skin firmness and overall appearance. Early-stage dermal injury (e.g., striae distensae) showed greater relative improvement compared with mature scars. POSAS scores decreased in representative cases, and the majority of the patients reported high satisfaction and willingness to undergo repeat treatment. No major adverse events were observed. Overall, 90% of patients expressed willingness to undergo repeat treatment, reflecting high satisfaction. Conclusions: PRP therapy demonstrated favorable outcomes in a real-life clinical setting, particularly in improving skin texture, firmness and overall skin appearance.